Influence of series RC circuit parameters on the streamer discharge process of gas spark switch. (November 2021) - Zheng, Shichao; Kang, Zhongjian; Li, Lei; Zhang, Anqi; Zhao, Kai; Zhou, Yaxun
Abstract: In this paper, the detailed streamer discharge process of argon spark switch at atmospheric-pressure has been numerically investigated with a 2-D fluid model. Two ball head electrodes with a rod-rod structure have been used, the DC voltage (10 kV) and series RC circuit were applied to the switch model. The distributions of microscopic parameters such as electron density, particle density and electron temperature at different time were obtained and analyzed, and the different streamer breakdown modes have been presented when the RC circuit parameters were changed. It is shown that in the case of RC (C = 0) circuit, the positive and negative streamers are formed on the two electrode heads and disseminate in the discharge gap, which finally develops into the positive and negative streamers breakdown. In the RC (C≠0) circuit, the electrons first gather from the surrounding to the anode. And then the positive streamer is formed on the anode terminal and quickly disseminate to the cathode terminal, which eventually develops into the positive streamer breakdown. In addition, the order of magnitude in current density and the breakdown time of voltage obtained by numerical simulation are closely matched with the experiment data. The results show that the present research might provide theoretical guidance of streamer discharge process of gas switch under series RC circuit. Highlights: The streamer discharge process and microscopic parameters distributions are simulated and analyzed in argon spark switch. The simulation results reveal that the different streamer breakdown modes and breakdown time scales. The 3-D schematic diagram better presents the gradient change of electron temperature in space. The current density data obtained by numerical simulation are approximately in agreement with the experimental results. The measured voltage curve describes the physics phenomena corresponding to the simulation model of streamer discharge.